2009
DOI: 10.1111/j.1540-8159.2009.02360.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Left Ventricle Diastolic Function on Natriuretic Peptides Levels in Patients with Atrial Fibrillation

Abstract: The increase of ANP/BNP concentration in patients with AF results not only from the presence of AF, but also reflects the impaired LV diastolic function. Natriuretic peptides, especially BNP, may be useful in diagnosing LV diastolic dysfunction in patients with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
(33 reference statements)
0
18
0
1
Order By: Relevance
“…Given the short half-life of BNP (23 min), its level significantly declined 2 h after AF recovered. This decrease was sustained until three months after the surgery, which indicates that the left atrial structure can undergo reverse remodeling after ablation (Ari et al, 2008;Bakowski et al, 2009;Kallergis et al, 2010;Wozakowska-Kapłon et al, 2010;Wozakowska-Kapłon, 2010). In the recurrent group, BNP levels were significantly higher than that in the successful group before ablation (P < 0.01) and significantly decreased 2 h after ablation (P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Given the short half-life of BNP (23 min), its level significantly declined 2 h after AF recovered. This decrease was sustained until three months after the surgery, which indicates that the left atrial structure can undergo reverse remodeling after ablation (Ari et al, 2008;Bakowski et al, 2009;Kallergis et al, 2010;Wozakowska-Kapłon et al, 2010;Wozakowska-Kapłon, 2010). In the recurrent group, BNP levels were significantly higher than that in the successful group before ablation (P < 0.01) and significantly decreased 2 h after ablation (P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…2). It has been speculated that baseline diastolic LV dysfunction may account for this observation [16]. However, this has not been established since Doppler echocardiography was not routinely performed to evaluate diastolic function.…”
Section: Discussionmentioning
confidence: 95%
“…BNP levels of patients with AF have been reported to be elevated, and they were associated with left ventricle diastolic dysfunction [13,14]. We also showed that BNP levels in acute stroke patients with AF were elevated, which indicated that such patients might have heart failure in the acute phase of stroke [15].…”
Section: Introductionmentioning
confidence: 82%